PROBLEMS OF INVESTIGATION OF ECONOMIC CRIMES COMMITTED BY OFFICIALS - Sattarov Ja'surbek Avazbekovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article explains that official crimes are considered an act that significantly harms the interests of a person, state and society with its level of danger, in addition to the fact that this type of crime has its own internal objective and subjective signs, first of all, leads to the penetration of organized crime into the activities of the public service, , it is indicated that analyzes have been carried out to slow down the processes of modernization of the country.